Lying for Who We Are: An Identity-Based Model of Workplace Dishonesty - Leavitt, Keith; Sluss, David M. (Academy of Management Review, 2015)
While the study of lying within organizations typically has focused on lies told for rational-instrumental purposes (such as lying for economic gain within negotiations), we argue that lying is a relatively common social-functional behavior embedded within ongoing workplace relationships. Drawing from social identity theory, we develop a theory of lying as a socially motivated behavioral response to identity threats at the personal, relational, or collective levels of identity in organizational life. Specifically, we propose that perceived identity threats undermine the unique fundamental identity motives at each level of self, and that as threat sensitivity and threat intractability increase, individuals become more likely to use lying as a threat management response in their interactions with other organizational members. Further, we propose that identity-based characteristics of organizational members with whom threatened individuals interact (i.e., the audience) determine the likelihood that lying will occur by assuaging or amplifying threats during identity enactment. Thus, by applying an identity lens to examine normatively unethical behavior, we develop a comprehensive model of everyday lying as socially motivated and identity-based behavior with implications for ongoing workplace relationships.